1996
DOI: 10.1042/bj3160093
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin potentiates activation of human platelets in association with JAK2 and TYK2 phosphorylation

Abstract: Thrombopoietin (TPO), also known as the c-mpl ligand, stimulates rapid tyrosine phosphorylation of multiple proteins in human platelets including the Janus family kinases JAK2 and TYK2. On its own, TPO has no effect on platelet aggregation and dense-granule secretion but induces a general potentiation of these responses by other stimuli. The most dramatic effect is observed against threshold concentrations of agonists for aggregation. Shape change or weak reversible aggregation induced by low concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Stimulation and measurements were performed at 37°C. Cytosolic Ca 2ϩ levels were measured as described previously (31). The intracellular Ca 2ϩ concentration was estimated using the equation described by Grynkiewicz et al (32): (R Ϫ R min )/(R max Ϫ R) ϫ K, where K represents the value K d ϫ Sf2/Sb2.…”
Section: Methodsmentioning
confidence: 99%
“…Stimulation and measurements were performed at 37°C. Cytosolic Ca 2ϩ levels were measured as described previously (31). The intracellular Ca 2ϩ concentration was estimated using the equation described by Grynkiewicz et al (32): (R Ϫ R min )/(R max Ϫ R) ϫ K, where K represents the value K d ϫ Sf2/Sb2.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that TPO does not elicit platelet aggregation or the release reaction by itself, but potentiates platelet activation induced by other agonists even in the presence of a cycloxygenase blocker [8,12,14], indicating that TPO enhances platelet activation irrespective of thromboxane A 2 formation. Since we found that TPO directly potentiated the activation of ERKs and MEKs in aspirinized platelets, we speculated that the TPO priming effect on ERKs and MEKs would be implicated in regulation of platelet functions by TPO without involvement of thromboxane A 2 formation.…”
Section: Discussionmentioning
confidence: 99%
“…In PDBu-stimulated platelets, TPO showed a similar dose-dependent effect on ERK2 activation (data not shown). Since TPO potentiates thrombin-induced release of A-granules and densegranules from platelets [11,13,14], we investigated whether the TPO effect on ERK2 was due to the potentiation of the release reaction. TPO potentiated the release reaction of A-granules and dense-granules induced by sub-maximal concentrations (0.025Ϫ 4, 7, 8, 11, 12) for 10 min, and treated with buffer (odd-numbered lanes) or 50 ng/ml TPO (even-numbered lanes) for 3 min before stimulation.…”
Section: Time Courses Of Erk2 and Pkc Activation Induced By Thrombin mentioning
confidence: 99%
See 1 more Smart Citation
“…18 The same patients however have tendency to a hemorrhagic rather than thrombotic diathesis. Alternative explanations for increased platelet activation include an effect of the JAK2-activating mutation, interaction of abnormal HCT, activated white cells, turbulent flow, or an increase in the known priming effect of thrombopoietin 19 due to elevated thrombopoietin levels. Recent data suggesting that JAK2 affects cMPL cell surface localization and stability 20 may also have implications for the pathogenesis of platelet activation.…”
Section: Platelet Activationmentioning
confidence: 99%